Biliary ascariasis from a rural setting: a case study. - Sai Sanjeev, M; Lum, LC (Penerbit UKM, 2012)
Ascariasis is a common helminthic infestation in Malaysia, particularly in rural settings. Ascariasis lumbricoides normally lives in the upper small bowel without causing symptoms. Complications arise when these worms migrate into the bile duct (biliary ascariasis). A case of biliary ascariasis presenting as biliary colic is described. Patient presented with 2 days duration of right upper quandrant pain at the district hospital. Initial investigations were suggestive of acute cholecystitis and patient was treated with empirical antibiotics. However, due to worsening symptoms, she was transferred to the nearest tertiary setting. The diagnosis of helminthic biliary infestation was established using both ultrasound of the hepatobiliary system (HBS), CT-Scan abdomen and endoscopic retrograde cholangiopancreatography (ERCP). Endoscopic removal of the worm led to rapid resolution of symptoms and patient was discharged home well.